Solvent-Free Melt-Drawing of Aligned Poly(L-Lactide-Co-ε-Caprolactone) Microfibres into Tubular Scaffold for Esophageal Tissue Engineering - Tan, Yu Jun (2016)
A solvent-free melt-drawing of aligned poly(L-lactide-co-ε-caprolactone) copolymer (PLC) microfibers into the tubular scaffold with the endocircular and exolongitudinal patterns has been investigated for the esophageal tissue engineering. The PLC microfibrous tubular scaffold was melt-drawn onto the 3D printed grooved mandrel. The experimental results show that the parallel grooves normal to the microfiber direction formed on the inner surface of the tubular scaffold. The surface topography of the tubular scaffold will mimic the endocircular and exolongitudinal muscle layers of the esophagus when the scaffold is turned inside out. It is proposed that this surface architecture may induce the cells orientation and cells attachment during its interaction with the individual smooth muscle cell. A large shrinkage of scaffold in dimension is observed along the fiber direction after the removal of scaffold from mandrel, which indicates that the PLC scaffold has a high elasticity. Therefore, the PLC scaffold will be mechanically compatible with the esophagus. Furthermore, it is suggested that the melt-drawing could be combined with the bioprinting technologies to print the tubular organs efficiently.